Divergent Dislocation of the Elbow in an Adult with Ehlers–Danlos Syndrome: A Case Report. Issue 3 (12th July 2021) - Onode, Ema; Takamatsu, Kiyohito; Kuroda, Takaaki; Kazuki, Kenichi; Nakamura, Hiroaki
Abstract : Case: A 32-year-old man with Ehlers–Danlos syndrome (EDS) fell while snowboarding and injured his right elbow. Radiography revealed a posterior dislocation of the elbow and a proximal radioulnar joint dislocation. A diagnosis of transverse divergent dislocation of the elbow was established. Open reduction and repair of the annular ligament, anterior oblique ligament, and capsule was performed with good clinical results. Conclusion: This is the first report of divergent dislocation of the elbow in an adult with EDS. Dislocation occurred without a fracture that required open reduction and internal fixation. The presence of soft-tissue fragility, hyperextension, and joint laxity peculiar to EDS are likely contributing factors to this phenomenon.